2004
DOI: 10.1038/sj.bjp.0705825
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive properties of CORM‐3, a novel water‐soluble carbon monoxide‐releasing molecule

Abstract: 1 Carbon monoxide (CO), one of the end products of heme catabolism by heme oxygenase, possesses antihypertensive and vasodilatory characteristics. We have recently discovered that certain transition metal carbonyls are capable of releasing CO in biological fluids and modulate physiological functions via the delivery of CO. Because the initial compounds identified were not water soluble, we have synthesized new CO-releasing molecules that are chemically modified to allow solubility in water. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
263
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(280 citation statements)
references
References 42 publications
11
263
2
3
Order By: Relevance
“…Identical results were obtained with depleted CORM-3 (data not shown), which is unable to release CO to myoglobin [10,29]. Moreover, we found that the increase in mitochondrial state 2 respiration by CORM-3 (20 µM) is blocked by the presence of myoglobin, a potent CO scavenger ( Figure 2A).…”
Section: Corm-3 Uncouples Mitochondrial Respiration At Low Micromolarsupporting
confidence: 66%
“…Identical results were obtained with depleted CORM-3 (data not shown), which is unable to release CO to myoglobin [10,29]. Moreover, we found that the increase in mitochondrial state 2 respiration by CORM-3 (20 µM) is blocked by the presence of myoglobin, a potent CO scavenger ( Figure 2A).…”
Section: Corm-3 Uncouples Mitochondrial Respiration At Low Micromolarsupporting
confidence: 66%
“…Although previous work has shown that iCORM-3 has much less effect than CORM-3 on biological material (8,17,34,37), very little has been done to elucidate bacterial viability with, and specific responses to, iCORM-3. The data presented herein show that iCORM-3 (made via incubation of CORM-3 in PBS) has virtually no effect on the growth of E. coli, whereas at the same concentration, CORM-3 readily inhibits growth (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ambiguity of its chemical structure, the iCORM-3 compound has been used in studies as a non-CO releasing control for CORM-3 (8,17,34,37) to test the reactivity of the Ru-compound when all labile CO has been removed. In all cases, iCORM-3 was shown to be much less reactive than the CO-RM.…”
mentioning
confidence: 99%
“…Thus, an artificial CO-donor produced a dose dependent relaxation of phenylephrine-precontracted aorta rings that was partially prevented by prior treatment with K ATP channels blocker glibenclamide (Foresti et al, 2004).…”
Section: Carbon Monoxide Ion Channels and Oxygen Chemoreceptionmentioning
confidence: 99%